Screening of Antibacterial MDR derived from Sponge Associated Fungus of Riung Water, Nusa Tenggara Timur - Khoeruddin Wittriansyah; Agus Trianto; Sekar Widyaningsih; Ocky Karna Radjasa; Rudhi Pribadi (Marine Science Department Diponegoro University, 2016)
Marine sponge-associated fungi are the sources of bioactive compounds with various pharmacologicals potency. This study aimed to isolate the sponge-associated fungi as the producer of the MDR anti-bacterial compounds. The associated fungi were isolated from the sponges collected from Riung water, Nusa Tenggara Timur. Five of the best isolates were cultured on MEA to obtain the methanolic extract for further studies. The antagonistic test was conducted using overlay method towards the MDR Staphylococcus aureus and Escherichia coli. A total of 33 fungi were isolated from 19 sponge specimens. The antagonistic test showed that 19 isolates were active against both S. aureus and E. coli, and 13 of them were merely active against one of the bacteria. However, only five isolates have strong activity against one or both of the bacteria. The KN-15-3 had the strongest activity against S. aureus (18.75±0.777mm) and E. coli (15.10±0.141mm) at the concentration of 400 μg.disc-1 so it can be developed further as a source of drug candicate. Keywords: Fungi symbiont, Sponges, MDR Antibacterial, Staphylococcus aureus, Escherichia coli.